Managing Public Expenditure A Reference Book for Transition Countries - Allen, Richard; Tommasi, Daniel; OECD eBooks (Paris : OECD Publishing, 2001)
Managing Public Expenditure presents a comprehensive and in-depth analysis of all aspects of public expenditure management from the preparation of the budget to the execution, control and audit stages. The book will be of general interest but is focused particularly on the needs of countries in transition, especially those in Central and Eastern Europe that seek to become members of the European Union. The book provides practical, operational information and guidance on all areas of public expenditure management, e.g. legal and institutional frameworks, preparation of the budget, implementation, cash management, performance management, accounting, financial information and reporting systems, internal control and internal audit, and external audit. Each part of the book ends with key points and directions for reform. The detailed questionnaire will help practitioners to identify the strong and weak elements in their budget systems so that they can take necessary remedial action. Managing Public Expenditure ends with a comprehensive glossary, bibliography and index. Richard Allen is an economist and spent most of his career at HM Treasury (the British Ministry of Finance), working mainly in the areas of fiscal policy, EU affairs, public expenditure management and international finance. He has also served as a diplomat in Washington DC and as a board member of the European Investment Bank. He was head of the budget and resource allocation team of the SIGMA Programme and is now adviser on governance at the Asian Development Bank. Daniel Tommasi is a Paris-based consultant in the the areas of fiscal policy, public expenditure management and macroeconomic management. He is an adviser to governments and a consultant for international organisations, including the World Bank, the Asian Development Bank, the United Nations Development Programme, and the European Union's Phare and Tacis Programmes. He has worked for over 25 years in some 30 countries in Central and Eastern Europe, the Middle East, Asia, the Pacific and Africa.
Forword -- Executive Summary -- Introduction. Reforming Public Expenditure: An Overview -- PART I. THE BUDGET AND THE INSTITUTIONAL CONTEXT -- Chapter 1. The Budget and its Coverage -- Chapter 2. The Legal and Institutional Framework -- Chapter 3. The European Budget and the Impact of EU Accession -- Summary Part I -- PART II. ALLOCATION OF RESOURCES  -- Chapter 4. Budget Classification, Presentation, and Programming -- Chapter 5. Policy Formulation and Budget Preparation -- Chapter 6. Multi-Year Budgeting and Investment Programming -- Summary Part II -- PART III. MANAGING BUDGET EXECUTION -- Chapter 7. The Budget Execution Cycle -- Chapter 8. Payables, Personnel, and Procurement Management -- Chapter 9. The Treasury Function and Cash Management -- Chapter 10. Internal Control and Internal Audit -- Summary Part III -- PART IV. ACCOUNTING, REPORTING AND AUDITING -- Chapter 11. Accounting -- Chapter 12. Financial Reporting -- Chapter 13. Financial Management and Information Systems -- Chapter 14. External Audit -- Chapter 15. Performance Management and Evaluation -- Summary Part IV -- Annex I. Questionnaire on Public Expenditure Management Systems -- Annex II. Establishment of a National Fund System -- Annex III. European Union Regulations Concerning Fiscal Surveillance, Budget, Financial Control, and Audit -- Annex IV. IMF Code of Good Practices in Fiscal Transparency -- Glossary -- Bibliography -- Selected Worldwide Web Sites -- Index
Keywords: Governance; Electronic books